Análisis estructural de tres comunidades forestales del Bajo Calima, Departamento del Valle del Cauca, Colombia - Vega Gutiérrez, German (UCR, San José (Costa Rica) CATIE, Turrialba (Costa Rica), 2014)
Tesis (Mag. Sc.) -- CATIE, Turrialba (Costa Rica) -- UCR, San José (Costa Rica), 1975